Screening of Drug-Induced Steatosis and Phospholipidosis Using Lipid Droplet-Selective Two-Photon Probes - Cho, Myoung Ki; Seo, Min Ji; Juvekar, Vinayak; Jo, Jae Hyung; Kim, Wontae; Choi, Kyeong Sook; Kim, Hwan Myung (Analytical Chemistry, 2020)
Lipid droplets (LDs) are organelles that play a major role in regulating the storage of neutral lipids. Dysregulation of LDs is associated with metabolic disorders, such as fatty liver diseases, obesity, diabetes, and atherosclerosis. We have developed LD-selective small-molecule fluorescence probes (probes 3 and 4) that are available for both one- A nd two-photon microscopy, employing live or fixed cells. We found that probes 3 and 4 sensitively detect the increased LDs in response to oleic acid or endoplasmic reticulum stress, both in cells and tissues of the liver. The narrow absorption and emission bands of probes 3 and 4 allow multicolor imaging for the study of the role of LDs in pathophysiology and LD-associated signaling by the coapplication of the probes for different organelles or antibodies against specific proteins. In addition, we show here, for the first time, that two-photon microscopy imaging using our LD-selective probes with LysoTracker provides a novel method for screening drugs to potentially induce steatosis and/or phospholipidosis.
Keywords: Absorption and emissions; Associated signaling; Endoplasmic reticulum stress; Fatty liver disease; Fluorescence probes; Metabolic disorders; Multicolor imaging; Two photon microscopy